On the Principle of Protection of Reliance Interests in Administrative Law - Ma, Nan (International Journal of Social Sciences and Public Administration, 2024)
Reliance on the principle of protection of interests first appeared in Germany, the German Administrative Procedure Act of 1976 established the principle as one of the basic principles of administrative law, and since then has undergone continuous development and improvement, and the development and improvement of the principle of protection of interests of the other civil law countries has had a far-reaching impact on the development and improvement of the principle of protection of interests of reliance. China’s research on the principle of protection of reliance interests started late, the implementation of the administrative licensing law in 2004, article 8 and article 69 is the first time in China to the principle of clarity, which shows that the Chinese government is committed to transforming the functions of the government, in order to effectively protect the administrative relative of the legitimate interests of the trust. The concept of building a country based on the rule of law in China has put forward higher requirements for government integrity, and the administrative organ should ensure the continuity and stability of its administrative behaviour, guarantee the legitimate expectations of citizens, and maintain the stability of social order. The government’s backtracking will cause incalculable damage to the government’s credibility and integrity image. The application of the principle of protection of reliance interests in China is not only a necessary element in promoting the construction of a government of integrity in China, but also an important condition for the construction of a modern state of law.